Advanced magnetic resonance techniques in early differentiation of pseudoprogression versus progression in the patients with glioblastoma multiforme - Mihailović, Jelena; Daković, Marko (Vojnosanitetski pregled, 2021)
Background/Aim. The diagnosis of glioblastoma multiforme progression may be confounded by a phenomena termed pseudoprogression (PSP) and pseudoresponse (RCT) which has become more common with the adoption of radiation therapy with concurrent and adjuvant application of temozolomide (CRT). Distinguishing of these phenomena is based on the follow-up scans since no single imaging method or technique is yet capable of performing their discrimination. In this study, we evaluated the dynamic susceptibility contrast (DSC perfusion) imaging and magnetic resonance (MR) spectroscopy to predict the prognosis and time to progression in the patients with glioblastoma multiforme. Methods. Fourty patients with primary glioblastoma multiforme were included in the analysis. The patients were examined in 3rd week after surgery and 10th week after the beginning of CRT. The MR exams were performed using the 1.5 T MR scanner (Avanto; Siemens, Erlangen, Germany). The maps of perfusion parameters and time-to-peak (TTP) parameter were calculated using the DPTools v3.79 software. The 3D CSI PRESS MR spectroscopy was performed in the area corresponding to the contrast enhancement on the T1W images. Results. Thirty-two of the 40 patients had progressive disease and 8 had pseudoprogression. Progressive disease showed the mean time of the peak values of 33 ± 7 s in 3rd and 30 ± 5 s in 10th week with no statistical significance between these two periods (p > 0.05). The patients with pseudoprogression showed the mean time of the peak values of 32 ± 8 s in 3rd week and 43 ± 9 s in 10th week; it was statistically significant difference (p < 0.05) was which favors better response to therapy. The spectroscopy results showed presence of glycine peak at 3.56 ppm in 6 patients with progressive disease which was not seen on spectra with pseudoprogression. Conclusion. The observed significant differences in the TTP values for PSP and RCT can provide basis for distinguishing two entities. The presence of glycine peak in the MR spectra could be a marker of RCT.